Infantile appendicitis: Importance of diagnostic accuracy and a lowered threshold for computed tomography - Raymond Okeke; Christian Saliba; Taylor Hallcox; Reeder Wells; Michaela Wycoff; Marc Simon; Alexandra Phocas; Erika M. Schmidt; Prajwal Keranalli; Tres Scherer; Shin Miyata; Christopher Blewett (Elsevier, 2022)
Appendicitis in the infant population is rare and often misdiagnosed. It can be associated with perforation and sepsis and necessitates expedient identification when present in a sick infant. We describe a case of perforated appendicitis in a 10-month-old infant after diagnostic workup ruled out common causes of colicky abdominal pain. We highlight documented recommendations for workup and management of neonatal and infantile appendicitis. We show that the consensus in literature is prompt diagnosis and surgical intervention for the best chance at preventing morbid outcomes that increase mortality.